Substrate curvature measurement system - Groenewald, Ben (Department of Electrical Engineering, 2016)
Industry often requires, in a variety of processes, the measurement of deformation induced in a solid object by mechanical stress. One such process is during the manufacture of very large scale integrated circuits (VLSI). During this process a substrate is coated with a thin film to protect the micro circuitry formed on the substrate. Due to the differences in thermal expansions between film and substrate, mechanical stresses can develop which may lead to deformation of the substrate surface. Any deformation of the substrate surface will result in mechanical stress in the interconnections of the circuitry, which could result in severe damage to the operation of the circuit. Different measurement techniques are available to measure the spherical deformation of substrates, with the latest known technique being a combination of a laser beam deflection and light scattering techniques. Many of the existing techniques reveal shortcomings, one of which is a 2-dimensional scanning capability with a minimum of moving components. Another shortcoming is the incapability of previous techniques to calculate the relative error which the measuring technique induces into the results. The aim of this study has been to develop an electro-optical system embodying the successful principles of these techniques in a system which will eliminate the shortcomings and produce results in excess of those previously recorded. In this work, we have concentrated on discussing the development of a system which will produce in situ real time monitoring of mechanical stresses in a solid. The system includes the minimization of system induced errors through the calculation of error voltage gains, and the introduction of a 2-dimensional scanning capability to determine the true position of the laser beam without prior knowledge of the initial substrate curvature. A four-quadrant position sensitive detector (PSD) with relevant Lab View software and programs were also introduced into the system.